The Isaacs, Concert Poster, October 27, 2024 - The Issacs (My University, 2024)
This poster advertises a concert featuring The Isaacs, a Grammy-nominated gospel group renowned for their blend of gospel, country, and bluegrass music. The Isaacs are celebrated for their multi-Dove Award-winning performances and their tribute to the Grand Ole Opry. The event is scheduled for October 20 at the Brooks County High School Performing Arts Center, located at 1801 Moultrie Highway, Quitman, Georgia. The poster outlines various sponsorship packages, ranging from $250 to $2000, which include tickets, program mentions, VIP seating, and meet-and-greet opportunities. Individual tickets are priced at $30. The event is sponsored by the Quitman-Brooks County Museum and Cultural Center, with a contact number provided for tickets and information.
This item contains: 1 PDF file and 1 JPG file
Keywords: Brooks County (Ga.); Music; Concert; Advertisement; Quitman (Ga.); Brooks County High School Performing Arts Center (Quitman, Ga.); Country music -- Performances.; Gospel music -- Performances.; Grand Ole Opry -- Tributes.; Isaacs (Musical group) -- Performances.; Music events -- Georgia -- Quitman.; Music sponsorship -- Georgia -- History.; Posters